University Students’ Changing Library Needs and Use: A Comparison of 2016 and 2018 Student Surveys - Scoulas, Jung Mi; De Groote, Sandra L. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This study examines differences in university students’ library use and satisfaction (e.g., in-person library visits, online and print resource use, space satisfaction, and library website use) between 2016 and 2018 based on local survey data. It also discusses how these findings provided guidance for future planning and action.    Methods – The academic university library developed the surveys for undergraduate and graduate students and distributed them in Spring 2016 and 2018. Both student surveys focused on examining students’ needs relative to library resources and services, although the 2018 student survey also attempted to quantify students’ library visits and their use of library resources. While the surveys were not identical, the four questions that appeared in both surveys (i.e., library visits, resource use, library space satisfaction, and library website use) were recoded, rescaled, and analyzed to measure the differences in both surveys.Results – The survey results reveal that students’ library visits and use of library resources in 2018 were higher than in 2016. In particular, undergraduate students’ use of library resources in 2016 were lower than those in 2018, whereas graduate students’ use of library resources remained similar in both years. Another key finding indicates that the mean score of students’ library quiet study space satisfaction in 2018 was higher than in 2016. However, when compared to the 2016 survey, there was a decrease in students’ ease of library website use in the 2018 survey.Conclusion – Assessing students’ behavior and satisfaction associated with their use of library physical spaces, resources, and services should be conducted on an ongoing basis. Over time, the survey findings can be used as evidence based data to communicate patterns of users’ behavior and satisfaction with various stakeholders, identify areas for improvement or engagement, and demonstrate the library’s impact. Survey results can also inform further strategic and assessment planning.